2011
DOI: 10.1155/2011/592567
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model of Oil Cracked Gas Resources and Its Application in the Gas Pools of Feixianguan Formation in NE Sichuan Basin, SW China

Abstract: The prediction of oil cracked gas resources is necessary and urgent in the gas exploration of these basins at high to over stage in China. A marine crude oil sample was pyrolyzed using sealed gold tubes system in our study. The pyrolysates including gas, liquid, and solid were quantitatively analyzed. Based on the pyrolysis data and kinetic calculation, the yield correlativity among gas, liquid, and solid products was regressed with high correlative coefficients to establish a prediction model suitable for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…4; Zhao et al, 2006). The oil-cracked gas resource for the Feixianguan Formation in NE Sichuan Basin, SW China was estimated based on the Wang et al (2007)'s prediction model (Wang et al, 2011). However, because the distribution of solid bitumen is inhomogeneous, we think that gas generation intensity (GGI, i.e., gas generation amount per unit area) is more helpful for assessing the size of oil-cracked gas reservoirs.…”
Section: Application Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4; Zhao et al, 2006). The oil-cracked gas resource for the Feixianguan Formation in NE Sichuan Basin, SW China was estimated based on the Wang et al (2007)'s prediction model (Wang et al, 2011). However, because the distribution of solid bitumen is inhomogeneous, we think that gas generation intensity (GGI, i.e., gas generation amount per unit area) is more helpful for assessing the size of oil-cracked gas reservoirs.…”
Section: Application Of the Resultsmentioning
confidence: 99%
“…Due to lack of data, the generation curve of pyrobitumen was speculated for the oil cracking at thermal maturity >2.8% EasyRo, but which is important for investigation of the lower Paleozoic paleo-reservoirs of southern China. Wang et al (2007Wang et al ( , 2011) suggested a prediction model of oil-cracked gas resources based on solid bitumen in reservoir and experimental results.…”
Section: Introductionmentioning
confidence: 99%